The E47 transcription factor negatively regulates CD5 expression during thymocyte development - Yang, Yang (National Academy of Sciences, 2004)
The expression of CD5 increases progressively as thymocytes mature. We have shown that CD5 expression is controlled by a tissue-specific regulatory promoter located upstream of the CD5 translation start sites. Deletion of this regulatory promoter, which contains three potential transcription factor binding sites (CCAAT, κE2, and ets) reduces the promoter activity to basal level. Of these sites, only ets proved essential for CD5 expression in T cell lines. Here, we introduce a role for the E47 transcription factor and the CD5 promoter κE2 site in regulating CD5 expression during thymocyte development. Using T cell lines, we show that (i) mutation of the κE2 site in the CD5 regulatory promoter results in a significant elevation of CD5 promoter activity; (ii) the E47 transcription factor binds to the κE2 site; and (iii) overexpression of E47 inhibits CD5 expression. We then show, in high-dimensional fluorescence-activated cell sorting studies with primary thymocytes at successive developmental stages, that (i) intracellular E47 levels decrease as surface CD5 expression increases; (ii) E47 expression is down-regulated and CD5 expression is correspondingly up-regulated in DN3 thymocytes in RAG-2-deficient mice injected with anti-CD3 to mimic pre-T cell receptor stimulation; and (iii) E47 expression is down-regulated and CD5 expression is up-regulated when double positive thymocytes are stimulated in vitro with anti-CD3. Based on these data, we propose that E47 negatively regulates CD5 expression by interacting with the κE2 site in the CD5 regulatory promoter and that decreases in E47 in response to developmental signals are critical to the progressive increase in CD5 expression as thymocytes mature.